Faktor-Faktor yang Berhubungan dengan Respiratory Distress pada Bayi Baru Lahir di Ruang Perinatologi RS X Jakarta - Setiowati, Theresia Dewi; Anggraeni, Lina Dewi; Rasmada, Sada (Jurnal Sehat Mandiri, 2023)
In newborns (BBL) respiratory disorders cause apnea, respiratory failure, to cardiac arrest and cause death. This study aims to determine the factors associated with respiratory distress in newborns in the perinatology ward of X Hospital from January 2018 to December 2020. The quantitative research method used an analytical survey approach (retrospective) and cross sectional design. The population is 795 BBL and the sample is 265 BBL using purposive sampling technique. The instrument used in the study was a medical record data collection form which contained data from the variables to be taken in this study.The bivariate analysis test used is the chi square test. The results of the study 56.6% of newborns experienced respiratory distress and came from a normal placental incidence of 94.7%; birth parity 1-3 times 95.1%; did not experience gestational diabetes 97.4% and women who were not pregnant 92.8%. The results of the bivariate test showed that there were no factors related to the occurrence of Respiratory Distress in newborns in the Perinatology room at X Hospital with a p-value> 0.05.Conclusion: placental factors, parity, diseases experienced by the mother and gemelli are not related to the incidence of respiratory distress in newborns at X Hospital. It is expected that health workers will provide counseling about respiratory distress so that pregnant women understand more and can minimize the impact on the survival of the baby who was born.